Huge adrenal myelolipoma: A rare entity - Pandey, G; Thakur, B; Devkota, M (Journal of Chitwan Medical College, 2015)
Adrenal myelolipoma is a benign uncommon tumor of adrenal gland which is mostly diagnosed incidentally. Huge adrenal myelolipoma are very rare. Histopathological examination gives the confirmed diagnosis. Here we present a 76 years old female with huge retroperitoneal mass, diagnosed as adrenal myelolipoma on the basis of histopathological examinations. Surgical management is the treatment of choice for large symptomatic tumors.